Temperature and refractive index measurement based on a coating-enhanced dual-microspheric fiber sensor. (22nd May 2018) - Ju, Yao; Ning, Shougui; Sun, Huijin; Mo, Jun; Yang, Chao; Feng, Guoying; Zhou, Hao; Zhou, Shouhuan
Abstract: We propose and demonstrate a coating-enhanced dual-microspheric structure fiber sensor that measures temperature and refractive index simultaneously. The claddings of the two microspheric structured fibers are spliced together and the ends of the fibers are coated with a layer of gold film to increase reflection, thereby forming a dual-microspheric structure sensor head. Our experimental results show that the temperature sensitivity and the refractive index can reach 65.77 pm °C −1 and −19.7879 nm RIU −1, respectively. Compared with the uncoated sensor, the refractive index sensitivity is significantly improved by the gold film. This work suggests a low-cost, high-resolution and convenient fiber-based method to achieve multifunctional sensing applications.